Functional adaptation to exercise in elderly subjects. - Brown, Annette (Curtin University, 2002)
Maintenance of physical function with advancing age is vital to continued independent living, which is highly valued by older people. Although commonly associated with the ageing process, loss of functional ability may well be accelerated by inactivity and subsequent decreasing physical capacities, such as muscle performance or balance abilities. The impact of increased levels of activity on physical performance and functional ability was investigated by a single blind randomised controlled study.Two intervention programs, one based on increased levels of physical activity and the second on increased levels of social activity, were provided to a group of community-living participants aged 75 years and over. Another group, receiving no intervention was also included. The exercise intervention offered twice weekly sessions of exercise over a 16-week period. This was designed and supervised by physiotherapists. The social intervention offered a weekly, two-hour session over 13 weeks. Baseline, post-intervention and follow-up assessments measured aspects of physical performance (muscle, balance, gait and step height performance) and functional ability (tiredness of limbs, mobility tiredness and the need for assistance with mobility and activities of daily living). In addition, all participants completed a monthly health and falls report. One hundred and forty-nine subjects were admitted into the study with 108 completing the intervention phase and all four assessments.Analysis of data indicated that the exercise intervention was effective in improving muscle performance (shoulder abduction mean difference 13.00, 95%CI 11.63-14.37; hip abduction mean difference 5.97, 95%CI 4.73-7.20; knee flexion mean difference 4.10, 95%CI 3.32-4.88; dorsiflexion mean difference 4.72, 95%CI 3.74-5.71), dynamic balance ability (Functional Reach mean difference 11.45, 95%CI 9.41-13.48), maximal gait speed (mean difference 0.62, 95%CI 0.50-0.74) and step height performance (mean difference 0.19, 95%CI 0.01-0.29). Improvements in dynamic balance and maximal walk performance were maintained for a period of four months following cessation of the intervention. The social program did not affect aspects of physical performance.Functional improvements were evident for both exercise and social subjects. Immediate improvements in limb tiredness (upper mean difference 0.37, 95%CI -0.11-0.84; lower mean difference 0.63, 95%CI 0.37-0.89) and mobility tiredness (mean difference 1.43, 95%CI 1.16-1.70) and activities of daily living dependence (mean difference 0.25, 95%CI -0.23-0.75) were demonstrated. Four and eight months later, exercise subjects had maintained the improvement in mobility tiredness and activities of daily living dependence. Mobility dependence showed a delayed improvement in both the exercise and social intervention participants. This improvement was not evident immediately following intervention, but emerged at both the four and eight month follow-up assessments.An intention to treat analysis (involving both completing and non-completing subjects) confirmed the usefulness of the exercise intervention as a strategy to improve and maintain functional ability in older subjects, specifically with regard to tiredness of the lower limbs, tiredness during mobility tasks and activities of daily living dependence. In addition, following the cessation of the exercise intervention, participants reported less mobility tiredness and dependence in activities of daily living tasks over the following eight-month period.The relationship between physical performance and functional ability indicated that muscle performance and limb tiredness were significantly associated. Decreased muscle performance of the upper limb was associated with reports of increased tiredness during functional activities involving the upper limb, such as combing hair and dressing the upper body. Similarly, decreased muscle performance of the lower limb, especially proximally, was associated with increasing tiredness of the lower limb during functional activities. Further, decreased proximal muscle performance of both the upper and lower limb was significantly associated with decreasing independence in the performance of physical activities of daily living. These results indicate the significant influence of muscle performance on functional ability, especially on tiredness of the limbs and activities of daily living dependence.The ability to predict future functional limitation, based on decreasing physical performance, was examined and shown to be of limited value. Hip muscle performance and changes in usual gait speed were poorly associated with increased lower limb tiredness and dependence in physical activities of daily living respectively. The lack of a robust relationship between variables of physical performance and functional ability measures indicates that loss of physical performance is not strongly associated with the development of functional limitations.Self-reported falls were monitored throughout the study. A significant increase in the number of participants reporting falls was evident in both the social intervention group and the control group throughout the study. In contrast, there was no change in the number of exercise participants reporting falls. These results suggest that the exercise intervention was effective at minimising the usual increase in the number of older people experiencing falls over time.The results of this study suggest that the exercise intervention program was effective in improving physical performance in elderly subjects. This also resulted in improved functional ability. Positive effects continued following completion of the program as improvements in mobility and activities of daily living tasks were demonstrated for a further eight months. By contrast, the social intervention program appeared to influence only the need for help with mobility tasks in the longer term.Increased physical activity, in the form of an exercise intervention program, specifically designed for community-living elderly people, can improve and maintain functional ability, both immediately and for up to eight months following the completion of the program. As such, involvement in exercise, even in the short-term, should be encouraged as a means of maintaining physical independence in later life. Therapists devising exercise programs specifically for older people should ensure that the associated outcome measures incorporate assessments of functional ability and not simply measures of impairment. This study has demonstrated that a real benefit of increased physical activity in older people may well be the increased physical independence associated with participation.